Utilization of solar energy in hydroponic systems for enhancing energy independence in farming communities - Lorenta In Haryanto; Tri Yuni Hendrawati; Darto Darto; Febri Yani; Firgi Adha Listanto; Dimas Yoga Pradipta Pratama (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Urban agriculture challenges, such as limited land and time constraints, make hydroponic technology ideal to support the development of sustainable agricultural systems. Water pumps are essential for distributing nutrient water to plants in a hydroponic system. Using solar panels as an alternative energy source for hydroponic water pumps reduces operational costs and supports energy conservation efforts. This project aims to implement solar panels on hydroponic water pump machines to create energy independence for farmer groups. The activities cooperated with a farmer group called Hidroponik Generik (HG) in Pesanggrahan from April to October 2024. The implementation method includes training and assistance in applying vertical hydroponic technology and training and assistance in solar power generation for hydroponic systems. Results from community service show that solar-powered pumps reduce electricity costs, enhance income potential, and support sustainable farming. An 800 WP solar panel provides 1600 WH daily, powering pumps for 12-13 hours, cutting electricity usage by 66 percent and reducing monthly expenses by 10 percent. Along with vertical hydroponic installation, this program increases farm income by 15 percent, with a 45 percent improvement in participants' understanding of solar technology. The results of the activities were deemed successful after the partners expressed satisfaction with the conducted activities.